Effect of co-solvent on biodiesel production using calcium aluminium oxide as a reusable catalyst and waste vegetable oil - Singh V.; Yadav M.; Sharma Y.C. (My University, 2025)
Calcium aluminium oxide (Ca2Al2O5) was synthesized via solid state method by using calcium carbonate and alumina calcined at 900 °C. The synthesized catalyst was characterized by TGA, XRD, FTIR, SEM, and BET. The particle size analysis and basicity test were also conducted. The catalyst was used for production of biodiesel using waste vegetable oil (WVO) as feedstock and methanol through transesterification. Acetone was used and reported as a co-solvent for the first time for synthesis of biodiesel. Effect of co-solvents on reaction parameters has been gaining concern for improvement of transesterification reaction. The reaction parameters such as weight (%) of co-solvent, molar ratio (oil:methanol), catalyst concentration, reaction time, temperature, and reusability of catalyst were studied. Highest conversion (97.98%) of biodiesel was obtained at 20 wt% of acetone, 1:6 M ratio (oil:methanol), 1.2 wt% calcium aluminate at 55 ± 1 °C for 25 min of reaction time. Calcium aluminate could be reused up to eight cycles with >75% FAME conversion at this cycle. Composition of crude WVO and respective FAME was analysed by GCMS technique. Physico-chemical properties of FAME such as acid value, cetane number, calorific value, flash point, fire point, viscosity, density, cloud point, pour point and ash content were evaluated and were found to be within ASTM standards. © 2017 Elsevier Ltd